The development of coffee cultivation in the traditional agroforestry of mixed-garden (dukuh lembur) to provide social-economic benefit for the Outer Baduy Community, South Banten, Indonesia - BUDIWATI S. ISKANDAR; JOHAN ISKANDAR; BUDI IRAWAN; SUROSO; Ruhyat Partasasmita (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Iskandar BS, Iskandar J, Irawan I, Suroso, Pasratasmita R. 2019. The development of coffee cultivation in the traditional agroforestry of mixed-garden (dukuh lembur) to provide social-economic benefit for the Outer Baduy Community, South Banten, Indonesia. Biodiversitas 20: 2958-2969. The Baduy community who resides in the Village of Kanekes, the Sub-district of Leuwidamar, the District of Lebak, South Banten has maintained the Sundanese tradition, particularly in practicing swidden farming (ngahuma). They practice swidden farming based on Traditional Ecological Knowledge (TEK) and belief. According to the Baduy tradition, the commercial plants, including coffee, clove, cacao, teak, and rubber have been prohibited to cultivate in Baduy area. However, because the population has increased rapidly and market economy has intensively penetrated the Baduy area, some commercial plants, including robusta coffee (Coffea canephora Pierre ex A. Froehner) have been introduced by the outer Baduy community. The objective of this study was to elucidate the traditional practice of the Outer Baduy in cultivating coffee trees that are integrated into the traditional agroforestry of mixed-garden (dukuh lembur or leuweung lembur). This study used qualitative method with some techniques of collecting data, including observation, participant observation, semi-structured interviews, and plant survey in the sample plots of the dukuh lembur. The results of the study showed that in 1980-s the robusta coffee plants were introduced by some Outer Baduy people and have since been planted in the dukuh lembur. In the past, because coffee was prohibited to be cultivated in Baduy area, the coffee trees were regularly cut during the purification of the Baduy tradition (pembersihan adat). Nowadays, however, the robusta coffee trees have been properly integrated into the existing dukuh lembur which is based on hybrid knowledge of TEK and scientific Western knowledge. The Outer Baduy coffee farming system has provided subsistence as a well commercial economy that may support the sustainability of the Outer Baduy swidden cultivation that is considered as the cultural identity of the Baduy community.